PCSK9 inhibition for the treatment of hypercholesterolemia: Promises and emerging challenges - Norata, Giuseppe; Tibolla, G.; Catapano, A. (2014)
Hypercholesterolemia, is a prominent risk factor for cardiovascular disease (CVD). Undestanding of the biochemical mechanisms that regulate the expression of the low density lipoproteins receptor (LDLR) and the hepatic clearance of LDL cholesterol (LDL-C) paved the way to the statin therapy as the gold standard for CVD prevention. The discovery of proteins that regulate - at a post-translational level - the activity of the LDLR has been a major breakthrough in developing new cholesterol-lowering drugs. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a key modulator of the LDLR degradation in the liver. Genetic studies confirmed that in humans PCSK9 mutations associate with hypercholesterolemia and hypocholesterolemia (gain-of-function or loss-of-function variants respectively). Moreover, PCSK9 is up-regulated by statin treatment and limits the efficacy of these agents. These findings led to the development of PCSK9 inhibitors. Anti-PCSK9 monoclonal antibodies showed encouraging results and are currently being evaluated in phase III clinical trials. The aim of this short review is to describe the new frontier of PCSK9 inhibition in the treatment of hypercholesterolemia. Emphasis here is given to critical emerging issues linked to PCSK9 physiology and pharmacology, which will require future investigation to definitely address the potential of anti-PCSK9 drugs in clinical practice. © 2014 Elsevier Inc.